Experimental study on purification of low concentration coalbed methane by hydrate method under amino acid system - Tian ZHAO; Yongliang XU; Lanyun WANG; Zecheng LYU; Xingwang HUO (Meitan kexue jishu, 2025)
The development and utilization of low-concentration gas resources is of great significance to alleviate the problems of energy shortage and unreasonable consumption structure. Leucine and tryptophan are highly effective green kinetic promoters to promote hydrate formation, in order to promote the rapid formation of hydrates, leucine and tryptophan were selected to study their methane hydrate formation promotion effects. However, their effects on coalbed methane separation by hydrate method in synergy with 1,3−dioxolane are not known. Amino acids are efficient green kinetic promoters for hydrate generation and can be used in gas storage and transportation technologies. In order to study the effect of both amino acids and the thermodynamic promoter 1,3−dioxolane on hydrate separation of low concentration CBM under synergistic effect, the kinetic process of hydrate generation and the gas separation efficiency of 30% CH4+70% N2 gas mixture under different volume fraction of additives system were investigated by using leucine, tryptophan, and 1,3−dioxolane as the additives and the effect of amino acids synergism on the hydrate morphology, induction time, gas consumption rate, gas consumption, gas separation efficiency under the synergistic effect of amino acids. The experimental results showed that the CH4 volume fraction in the gas resulting from hydrate decomposition was greatly improved compared with that of the feed gas, and the CH4 volume fraction in the decomposed gas ranged from 43.92% to 57.41%, the CH4 recovery rate was from 42.11% to 62.20%, and all the systems were able to efficiently separate the CH4 gas in the mixture of 30% CH4+70% N2. Among them, when the pressure was 6 MPa, the separation and purification of CH4+N2 in the 0.3 wt% leucine + 1 mol% 1,3−dioxolane complex system was the best, with a CH4 volume fraction of 56.46% and a recovery of 64.2%. Compared with the single 1,3−dioxolane system, the complex system with the addition of leucine and tryptophan further enhanced the separation and purification of 30% CH4+70% N2, which has good application prospects and provides a theoretical basis for the development and utilization of low concentration coalbed methane.